Half of the habitat of Australia's highly imperilled narrow-range species is outside protected areas - Michelle Ward; Martine Maron; Jeremy S. Simmonds; Mark Lintermans; Nick S. Whiterod; David G. Chapple; Hugh P. Possingham; Sarah M. Legge; Rachael V. Gallagher; Brendan A. Wintle; Samantha Vine; Kita Ashman; et al. (Biological Conservation, 2025)

Recommendations for quantitative uncertainty consideration in ecology and evolution - Emily G. Simmonds; Kwaku P. Adjei; Benjamin Cretois; Lisa Dickel; Ricardo González-Gil; Jack H. Laverick; Caitlin P. Mandeville; Elizabeth G. Mandeville; Otso Ovaskainen; Jorge Sicacha-Parada; Emma S. Skarstein; Bob O'Hara (Trends in Ecology & Evolution, 2024)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Correction to: Recommendations for the nomenclature of enteroviruses and rhinoviruses - P. Simmonds; A. E. Gorbalenya; H. Harvala; T. Hovi; N. J. Knowles; A. M. Lindberg; M. S. Oberste; A. C. Palmenberg; G. Reuter; T. Skern; C. Tapparel; K. C. Wolthers; et al. (Archives of Virology, 2020)
Unfortunately, one of the affiliations of author “A. E. Gorbalenya” was missed in original version. The affiliation is updated here.

Design catalogue for eco-engineering of coastal artificial structures: a multifunctional approach for stakeholders and end-users - Kathryn A. O’Shaughnessy; Stephen J. Hawkins; Ally J. Evans; Mick E. Hanley; Paul Lunt; Richard C. Thompson; Robert A. Francis; Simon P. G. Hoggart; Pippa J. Moore; Gregorio Iglesias; David Simmonds; James Ducker; et al. (Urban Ecosystems, 2020)
Coastal urbanisation, energy extraction, food production, shipping and transportation have led to the global proliferation of artificial structures within the coastal and marine environments (sensu “ocean sprawl”), with subsequent loss of natural habitats and biodiversity. To mitigate and compensate impacts of ocean sprawl, the practice of eco-engineering of artificial structures has been developed over the past decade. Eco-engineering aims to create sustainable ecosystems that integrate human society with the natural environment for the benefit of both. The science of eco-engineering has grown markedly, yet synthesis of research into a user-friendly and practitioner-focused format is lacking. Feedback from stakeholders has repeatedly stated that a “photo user guide” or “manual” covering the range of eco-engineering options available for artificial structures would be beneficial. However, a detailed and structured “user guide” for eco-engineering in coastal and marine environments is not yet possible; therefore we present an accessible review and catalogue of trialled eco-engineering options and a summary of guidance for a range of different structures tailored for stakeholders and end-users as the first step towards a structured manual. This work can thus serve as a potential template for future eco-engineering guides. Here we provide suggestions for potential eco-engineering designs to enhance biodiversity and ecosystem functioning and services of coastal artificial structures with the following structures covered: (1) rock revetment, breakwaters and groynes composed of armour stones or concrete units; (2) vertical and sloping seawalls; (3) over-water structures (i.e., piers) and associated support structures; and (4) tidal river walls.

Recommendations for the nomenclature of enteroviruses and rhinoviruses - P. Simmonds; A. E. Gorbalenya; H. Harvala; T. Hovi; N. J. Knowles; A. M. Lindberg; M. S. Oberste; A. C. Palmenberg; G. Reuter; T. Skern; C. Tapparel; K. C. Wolthers; et al. (Archives of Virology, 2020)
Enteroviruses (EVs) and rhinoviruses (RVs) are significant pathogens of humans and are the subject of intensive clinical and epidemiological research and public health measures, notably in the eradication of poliovirus and in the investigation and control of emerging pathogenic EV types worldwide. EVs and RVs are highly diverse in their antigenic properties, tissue tropism, disease associations and evolutionary relationships, but the latter often conflict with previously developed biologically defined terms, such as “coxsackieviruses”, “polioviruses” and “echoviruses”, which were used before their genetic interrelationships were understood. This has created widespread formatting problems and inconsistencies in the nomenclature for EV and RV types and species in the literature and public databases. As members of the International Committee for Taxonomy of Viruses (ICTV) Picornaviridae Study Group, we describe the correct use of taxon names for these viruses and have produced a series of recommendations for the nomenclature of EV and RV types and their abbreviations. We believe their adoption will promote greater clarity and consistency in the terminology used in the scientific and medical literature. The recommendations will additionally provide a useful reference guide for journals, other publications and public databases seeking to use standardised terms for the growing multitude of enteroviruses and rhinoviruses described worldwide.

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Evidence of host-associated divergence from coral-eating snails (genus Coralliophila) in the Coral Triangle - Sara E. Simmonds; Vincent Chou; Samantha H. Cheng; Rita Rachmawati; Hilconida P. Calumpong; G. Ngurah Mahardika; Paul H. Barber (Coral Reefs, 2018)

Ratification vote on taxonomic proposals to the International Committee on Taxonomy of Viruses (2015) - M. J. Adams; E. J. Lefkowitz; A. M. Q. King; D. H. Bamford; M. Breitbart; A. J. Davison; S. A. Ghabrial; A. E. Gorbalenya; N. J. Knowles; P. Krell; R. Lavigne; D. Prangishvili; et al. (Archives of Virology, 2015)

AGAGE Observations of Methyl Bromide and Methyl Chloride at Mace Head, Ireland, and Cape Grim, Tasmania, 1998–2001 - P. G. Simmonds; R. G. Derwent; A. J. Manning; P. J. Fraser; P. B. Krummel; S. O'Doherty; R. G. Prinn; D. M. Cunnold; B. R. Miller; H. J. Wang; D. B. Ryall; L. W. Porter; et al. (Journal of Atmospheric Chemistry, 2004)

Hydroxyl Radical Concentrations Estimated from Measurements of Trichloroethylene during the EASE/ACSOE Campaign at Mace Head, Ireland during July 1996 - R. G. Derwent; N. Carslaw; P. G. Simmonds; M. Bassford; S. O'Doherty; D. B. Ryall; M. J. Pilling; A. C. Lewis; J. B. McQuaid (Journal of Atmospheric Chemistry, 1999)

Classification, nomenclature, and database development for hepatitis C virus (HCV) and related viruses: proposals for standardization - B. Robertson; G. Myers; C. Howard; T. Brettin; J. Bukh; B. Gaschen; T. Gojobori; G. Maertens; M. Mizokami; O. Nainan; S. Netesov; K. Nishioka; et al. (Archives of Virology, 1998)

Methyl Sulphone Metabolites of Polychlorinated Biphenyls (PCBs) in Cetaceans from the Irish and the Aegean Seas - G. M. Troisi; K. Haraguchi; M. P. Simmonds; C. F. Mason (Archives of Environmental Contamination and Toxicology, 1998)

On the Spatial Distribution and Seasonal Variation of Lower-Troposphere Ozone over Europe - H. E. Scheel; H. Areskoug; H. Geiss; B. Gomiscek; K. Granby; L. Haszpra; L. Klasinc; D. Kley; T. Laurila; A. Lindskog; M. Roemer; R. Schmitt; et al. (Journal of Atmospheric Chemistry, 1997)

Segregation and Interpretation of Ozone and Carbon Monoxide Measurements by Air Mass Origin at the TOR Station Mace Head, Ireland from 1987 to 1995 - P. G. Simmonds; S. Seuring; G. Nickless; R. G. Derwent (Journal of Atmospheric Chemistry, 1997)